2023
DOI: 10.21203/rs.3.rs-2631484/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ninety-degree angled collimator: a dosimetric study related to dynamic intensity-modulated radiotherapy in patients with endometrial carcinoma

Abstract: Background Our purpose was to ensure that the dose constraints of the organs at risk (OARs) were not exceeded while increasing the prescription dose to the planning target volume (PTV) from 45 Gy to 50.4 Gy with the dynamic intensity-modulated radiotherapy (IMRT) technique. While trying for this purpose, a new dynamic IMRT technique that named 90° angled collimated dynamic IMRT (A-IMRT) planning was developed by us. Methods This study was based on the computed tomography data sets of 20 patients with postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…In another study, Serarslan and colleagues compared the dosimetric differences using physical WB-CRT, field-in-field IMRT and IMRT. 15 Techniques were evaluated with respect to expected target volume coverage and the dose to OAR. They suggested that IMRT was superior to WB-CRT ( p = 0·005 for the V 20 for the right kidney; p = 0·001 for the D-mean in the left kidney; p = 0·023 for the V 20 for the left kidney).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Serarslan and colleagues compared the dosimetric differences using physical WB-CRT, field-in-field IMRT and IMRT. 15 Techniques were evaluated with respect to expected target volume coverage and the dose to OAR. They suggested that IMRT was superior to WB-CRT ( p = 0·005 for the V 20 for the right kidney; p = 0·001 for the D-mean in the left kidney; p = 0·023 for the V 20 for the left kidney).…”
Section: Discussionmentioning
confidence: 99%
“…CI is defined by a ratio of reference isodose volume to target volume of PTV. 15 The value of CI varies between 0 and 1, and a value closer to one indicates better conformity of dose to the PTV. The 95% isodose volume was taken as the reference volume of the PTV.…”
Section: Methodsmentioning
confidence: 99%